2005
DOI: 10.1002/tox.20117
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and temporal variation of Microcystis species composition and microcystin concentration in Lake Biwa

Abstract: Spatial and temporal variation in Microcystis species composition and microcystin concentration, quantified by enzyme-linked immunosorbent assay and high-performance liquid chromatography, were investigated during a 3-year period (1998-2000) in the Northern Basin of Lake Biwa. The Northern Basin generally had a concentration of 5 microg L(-1) or less, except at station 1 (Nagahama Bay) from July to October during the study period. The maximum concentration at station 1 was 22.7, 35.9, and 22.0 microg L(-1) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 25 publications
(28 reference statements)
6
35
1
1
Order By: Relevance
“…M. viridis dominated almost throughout the study, and the proportion of total Microcystis varied between 35% and 87%. Even though M. viridis was predominant, the amounts of MCs it produced were low (Harada et al, 2001;Ozawa et al, 2005), and our results generally were consistent with observations from above studies.…”
Section: Explanation Of the Dynamics Of Extracellular MC Concentrationssupporting
confidence: 93%
See 2 more Smart Citations
“…M. viridis dominated almost throughout the study, and the proportion of total Microcystis varied between 35% and 87%. Even though M. viridis was predominant, the amounts of MCs it produced were low (Harada et al, 2001;Ozawa et al, 2005), and our results generally were consistent with observations from above studies.…”
Section: Explanation Of the Dynamics Of Extracellular MC Concentrationssupporting
confidence: 93%
“…The study above had indicated the dominant Microcystis species were identified as M. wesenbergii, M. ichthyoblabe and M. viridis. M. wesenbergii was one of the most dominant waterbloom-forming microcystis morphospecies from May to December (ranged between 25% and 42%), but were not shown to contain MC synthesis gene or MC by both molecular and chemical methods (Xu et al, 2008a(Xu et al, , 2008bOzawa et al, 2005). M. viridis dominated almost throughout the study, and the proportion of total Microcystis varied between 35% and 87%.…”
Section: Explanation Of the Dynamics Of Extracellular MC Concentrationsmentioning
confidence: 97%
See 1 more Smart Citation
“…On September 13, 2006, cell numbers were much more than that of on August 28, but the maximum MC value occurred on August 28. Heresztyn and Nicholson [19] reported the toxin concentration followed the general trend of cyanobacterial cell numbers, whereas other studies found no relationship between Microcystis cell numbers and MC concentrations with changes in MC concentrations related to the dominant species of Microcystis [20]. However, in the present study, the MC content within the cyanobacteria and in water sample was consistent.…”
Section: Contents and Species Of Microcystin In Water Samplescontrasting
confidence: 45%
“…In summary, it is reasonable to ignore the effect of turbulence on colony viability and size in simulation process, and simulated results are suitable for field. The phenomenon has been found that water blooms occurred under poor weather or nutrient conditions (Ozawa et al, 2005;Ma et al, 2015). The reason may be explained as the effect of water motion.…”
Section: Discussionmentioning
confidence: 99%